Two Classes of GABAergic Neurons in the Inferior Colliculus - Ito, Tetsufumi (Society for Neuroscience, 2009)
The inferior colliculus (IC) is unique, having both glutamatergic and GABAergic projections ascending to the thalamus. Although subpopulations of GABAergic neurons in the IC have been proposed, criteria to distinguish them have been elusive and specific types have not been associated with specific neural circuits. Recently, the largest IC neurons were found to be recipients of somatic terminals containing vesicular glutamate transporter 2 (VGLUT2). Here, we show with electron microscopy that VGLUT2-positive (VGLUT2(+)) axonal terminals make axosomatic synapses on IC neurons. These terminals contain only VGLUT2 even though others in the IC have VGLUT1 or both VGLUT1 and 2. We demonstrate that there are two types of GABAergic neurons: larger neurons with VGLUT2(+) axosomatic endings and smaller neurons without such endings. Both types are present in all subdivisions of the IC, but larger GABAergic neurons with VGLUT2(+) axosomatic terminals are most prevalent in the central nucleus. The GABAergic tectothalamic neurons consist almost entirely of the larger cells surrounded by VGLUT2(+) axosomatic endings. Thus, two types of GABAergic neurons in the IC are defined by different synaptic organization and neuronal connections. Larger tectothalamic GABAergic neurons are covered with glutamatergic axosomatic synapses that could allow them to fire rapidly and overcome a slow membrane time constant; their axons may be the largest in the brachium of the IC. Thus, large GABAergic neurons could deliver IPSPs to the medial geniculate body before EPSPs from glutamatergic IC neurons firing simultaneously.